2008
DOI: 10.1111/j.1365-2818.2008.02051.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of atomic force microscopy to the study of natural and model soil particles

Abstract: Summary The structure and surface chemistry of soil particles has extensive impact on many bulk scale properties and processes of soil systems and consequently the environments that they support. There are a number of physiochemical mechanisms that operate at the nanoscale which affect the soil's capability to maintain native vegetation and crops; this includes soil hydrophobicity and the soil's capacity to hold water and nutrients. The present study used atomic force microscopy in a novel approach to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…These techniques have been employed to study the topography and conformational structures of HS on solid surface [47][49] as well as protein complexes formed with soil or HS [23], [50]. We used mica as substrate because its surface properties are similar to those of minerals present in terrestrial environments.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques have been employed to study the topography and conformational structures of HS on solid surface [47][49] as well as protein complexes formed with soil or HS [23], [50]. We used mica as substrate because its surface properties are similar to those of minerals present in terrestrial environments.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with what has been already observed for mineral particles from soils and groundwaterexposed minerals. [23][24][25] For example, Cheng et al (2008) 25 observed an increased sample roughness for humic acid deposited on acid-washed quartz sand, although an opposite trend was observed for mineral quartz particles from soil with increasing organic matter content. SOM has also been previously reported to collect in the rougher areas of soil particle surfaces, 8 thus further increasing local roughness, which in turn has an effect on soil wettability through the Cassie-Baxter effect.…”
Section: Nanoscale Communicationmentioning
confidence: 99%
“…AFM adhesion data, which shows higher values for APW compared to CON samples (Fig. 3D), has been previously used to assess hydrophilicity states of several substrates with both silicon and silicon nitride tips: 25,27,28 sample hydrophilicity is expected to be associated with evident AFM pull-off adhesion values due to the formation of a water meniscus between the cantilever tip and the sample surface, 29 as schematically shown in Fig. S3A.…”
Section: Nanoscale Communicationmentioning
confidence: 99%
“…Much smaller scale measurements of soil particle bonding are feasible with atomic force microscopy (AFM), which has been applied to measure the effects of humic acids (Cheng et al, 2008) and polysaccharides produced by ectomycorrhizal fungi (Gazze et al, 2013) on the roughness of soil particles at nanometer resolution, as well as the thermal behavior of soil organic materials (Schaumann and Mouvenchery, 2012). Great potential exists to study particle bonding caused by specific biological compounds in soil using AFM.…”
Section: Engineering Of Vadose Zone Physical Properties By Soil Biologymentioning
confidence: 99%